2002
DOI: 10.1055/s-0037-1613237
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of Recombinant Murine Factor VIII

Abstract: SummaryHemophilia A is the inherited bleeding disorder that results from mutation of blood coagulation factor VIII (fVIII). Described here is the generation of a regulated expression system producing recombinant murine fVIII. Murine B-domainless fVIII was expressed at a peak level of 4 units/106 cells/24 h in serum-free media. Subsequently, a two-step purification procedure resulted in 5,300-fold enrichment and a 70% yield. Highly purified recombinant murine fVIII had a specific coagulant activity of 660 units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 42 publications
2
78
0
Order By: Relevance
“…Taken together the results in COS-7 and BHK-M cells indicate that the porcine A1 and ap-A3 domains in HP fVIII cDNAs are necessary and sufficient to produce expression levels equivalent to rp-fVIII. Expression of MP fVIII Constructs-We previously showed that a recombinant B domain-deleted murine fVIII designated rm-fVIII expresses at lower levels than rh-fVIII in BHK-M cells (23). Because the porcine A1 and ap-A3 domains confer high level expression in human/porcine fVIII hybrids, we wanted to address whether they increase expression when substituted into murine fVIII.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together the results in COS-7 and BHK-M cells indicate that the porcine A1 and ap-A3 domains in HP fVIII cDNAs are necessary and sufficient to produce expression levels equivalent to rp-fVIII. Expression of MP fVIII Constructs-We previously showed that a recombinant B domain-deleted murine fVIII designated rm-fVIII expresses at lower levels than rh-fVIII in BHK-M cells (23). Because the porcine A1 and ap-A3 domains confer high level expression in human/porcine fVIII hybrids, we wanted to address whether they increase expression when substituted into murine fVIII.…”
Section: Resultsmentioning
confidence: 99%
“…Generation of Hybrid fVIII cDNAs-The synthesis of B domaindeleted human, porcine, and murine cDNA constructs, designated rhfVIII, rp-fVIII, and rm-fVIII, in the mammalian expression vector ReNeo has been described previously (19,23). These constructs contain a nucleotide sequence between the A2 and ap-A3 domains encoding a linker region of human, porcine, or murine origin (designated SQ, OL, or SQ, respectively), which includes the Arg-His-Gln-Arg recognition sequence for PACE/furin processing (24,25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The faster human A2 subunit dissociation rate may be an evolutionary adaptation, perhaps associated with the development of an upright posture and venous stasis in the lower extremities. In this regard it is interesting to note that the half-life of murine fVIIIa at 23°C is greater than 30 min, compared with ϳ2 and 7 min for human and porcine fVIIIa, respectively (50).…”
Section: Discussionmentioning
confidence: 98%
“…The transfected cells were cultured in serum free media. The medium was subjected to a two-step ion exchange chromatography (22). The factor VIII-containing medium was loaded on a HiPrep 16/10 SP FF column (Amersham Biosciences) and eluted using a linear gradient from 100 -650 mM NaCl in HEPES-CaCl 2 buffer containing 10 mM OPLS.…”
Section: Preparation Of Rfviii⅐opls Complexesmentioning
confidence: 99%